SPOŁECZNE ASPEKTY STOSOWANIA „ZASADY” INTEGRALNOŚCI WYROKU ROZWODOWEGO - Holewińska-Łapińska, Elżbieta (Zeszyty Prawnicze, 2017)
Social Aspects of Implementing the Rule of Integrity of a Divorce Verdict Summary The provisions regulating a divorce are binding on the whole Polish territory since 1 January 1946 The main consequences of adjudging a divorce should be included in the divorce verdict, and the court decides on them ex officio. At present the court states ex officio whether and which of the spouses is guilty for the breakdown of the marriage (the court is entitled to leave the issue without a decision at the mutual request of both parties) as well as the parental authority over a minor child, the costs of providing for a child and his upbringing and if the spouses share an apartment, the court also decides on the manner of its use (art. 57, 58 § 1 and 2 of the Family and Custody Code). It is an unquestionable and commonly accepted concept that appealing a primary decision on a dissolution of the marriage prevents other court’s orders being a consequence of a divorce from becoming effective. The „rule” of integrity of a divorce verdict assumes, however, that it is necessary to reverse a whole judgment in the appeals proceedings if there are basis to overrule one of the decisions included therein (e.g. regarding guilt, parental authority) As a consequence, if a different order than a decision on a divorce has been appealed the verdict in the part that has not been appealed cannot become valid. Such an understanding of the „rule” of integrity of a divorce verdict is a result of the considerations on the social consequences of a divorce for a family. The article presents the doctrine and the verdicts of the Supreme Court which contributed to working out this understanding. They realize efficiently the concept of a divorce included in the Family and Custody Code. In the second half of the 90s of the XX century the concept of the rule of integrity of a divorce verdict widely understood started to raise doubts in connection with the changes in the civil proceedings which strengthened dispositiveness (dyspozytywnosc) and the adversary character of the proceedings. At the same time it was observed in Poland that the numer of weddings decreased, more couples started to live in informal relations, there was a massive increase of children born out of a wed-lock as well as the increase in number of the divorce matters filed with courts. The author invites to a discussion on the Polish divorce law in the light of the changes in the model of a Polish family and attitudes towards divorces and heterosexual cohabitation. The purpose of realization of the „rule” of integration of the divorce verdict should be one of the elements of this discussion. Its acceptance should lead to amendments to the Code of Civil Proceedings (with regard to appealing a verdict on a divorce) related to the concept of validity of a verdict, material scope of the appeals court’s recognition and the interdiction of reformationis in peius. The present law makes the rule impossible to realize when the dissolution of the marriage was appealed. The drafts of the divorce law that are presented in literature aim at its liberalization. Applying the „rule” of the integrity of a divorce verdict hinders obtaining a divorce.